Dictionary of national biography: 1951 - 1960 (London, England Oxford University Press, 1972)
The Dictionary of National Biography (DNB) is a standard work of reference on notable figures from British history, published since 1885. The people whose biographies are in this volume died between January 1, 1951 and December 31, 1960.
"With an Index covering the years of 1901 - 1960 in one alphabetical series" on title page.
45113
Keywords: Dictionaries -- Biographies; Biographies -- 1951 - 1960 -- Britain